2023
DOI: 10.1002/adfm.202302332
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Proton Supply/Filtration Regulates the Dynamics of Electrocatalytic Nitrogen Reduction Reaction: A Perspective

Abstract: As a promising energy carrier, ammonia synthesis by electrocatalytic nitrogen reduction reaction (eNRR) is a promising green and low‐carbon ammonia synthesis strategy that can replace the traditional Haber–Bosch process. However, the development of eNRR processes is mainly severely constrained by competitive hydrogen evolution reaction (HER), and the corresponding strategies to inhibit this adverse side reaction to obtain high eNRR selectivity are still limited. In addition, for this complex reaction involving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…Boric acid can serve as both an acceptor and a donor for hydrogen bonding. The boron atom possesses a robust electron-attracting ability for the boric acid molecule, which results in the bonding electron cloud of the oxygen atom in the B–O bond being biased toward the boron atom and less likely interacting with the hydrogen atom in the O–H bond of the alcohol molecule. Consequently, at the 010 crystalline facet of boric acid, the oxygen atom in the alcohol molecule is more stable in the configuration facing the hydrogen atom in the boric acid molecule (Figure S5–S7).…”
Section: Resultsmentioning
confidence: 99%
“…Boric acid can serve as both an acceptor and a donor for hydrogen bonding. The boron atom possesses a robust electron-attracting ability for the boric acid molecule, which results in the bonding electron cloud of the oxygen atom in the B–O bond being biased toward the boron atom and less likely interacting with the hydrogen atom in the O–H bond of the alcohol molecule. Consequently, at the 010 crystalline facet of boric acid, the oxygen atom in the alcohol molecule is more stable in the configuration facing the hydrogen atom in the boric acid molecule (Figure S5–S7).…”
Section: Resultsmentioning
confidence: 99%
“…However, current research has demonstrated that the mechanism of heterogeneous catalytic e‐NRR at the interface remains a subject of debate, with the two main proposed mechanisms being the dissociation mechanism (Figure 2a) and the association mechanism (Figure 2c and 2d). [6a,11] The dissociation mechanism, exemplified by the Haber‐Bosch process, involves breaking the N≡N bond before the hydrogenation reaction, thus necessitating a substantial energy input. Conversely, the e‐NRR processes on various catalyst surfaces predominantly follow the association mechanism, where the N≡N bond breaks simultaneously with the release of the first ammonia molecule.…”
Section: Catalyst Designmentioning
confidence: 99%
“…[10] Prior to the e-NRR to ammonia process, nitrogen needs to be dissolved into the electrolyte and cross the solid-liquid interface to reach the catalyst surface. [11] Therefore, both the inherent properties of the electrolyte and the microenvironment of the solid-liquid interface also have a great influence on the nitrogen reduction performance. In this concept article, the strategies to enhance the performance of e-NRR to ammonia are summarized and analyzed from three perspectives: the design of catalysts, the modification of reaction interfaces, and the reaction system modulation (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While numerous catalysts for NRR have emerged in aqueous solutions, challenges arise due to the limited solubility, diffusion, and chemical inertness of N 2 , compounded by the presence of the hydrogen evolution side reaction (HER), thereby impeding industrialization efforts. More importantly, some researchers have raised concerns about the potential experimental false positives in water-based systems, as synthesized ammonia could originate from external sources of pollution. …”
mentioning
confidence: 99%